Fish Seed Procurement and Fish Production Trends in Rajasthan - N.C. Ujjania; L.L. Sharma; C.P. Juyal (Journal of Indian Fisheries Association, 2023)
In this paper, fish seed procurement and fish production trends of the Rajasthan state are analyzed. The state is blessed with ample fisheries resources in the form of reservoirs, lakes, rivers, canals etc. which contributed to produce 54,035 metric tonnes fishes in the fishing year 2017-18. The average numbers of seed stocked and fish production during 1997- 98 to 2017-18 were 477 million fry and 26,016 metric tonnes, respectively, depicting an average growth rate of 10.50 % and 7.22 %. During the same period, production variability was 67.31 and 50.67 and growth rate variability of 210.00 and 162.79, respectively. The second order polynomial function shows as best fit equations for fish seed procurement ( y = 3 . 3 2 3 3 x 2 – 2 9 . 3 7 4 x + 2 7 6 . 2 8 ) a n d f i s h p r o d u c t i o n (y=116.27x2–550.52x+13740). The regression equation for these variables (fish production on seed production) was y = 43.141x + 5431.7 which depicted that addition of one million fry can increase 43.141 metric tonnes of fish production. Further, the correlation co-efficient (r=0.9468) of these variables showed a significant positive relationship. These findings also revealed that available seed quantity is not sufficient to stock the water bodies of the state, in view of this, it is suggested to promote the seed production and rearing facilities within state which may help to enhance the optimum utilization of the water bodies and yet maintaining a sustainable capture fisheries and to encourage fish farming in the state.